Cardiovascular Risk Assessement in Osteoporotic Patients Using Osteoprotegerin as a Reliable Predictive Biochemical Marker - Rasheed, Noora Wael; Taresh, Ooroba Jameel (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Some studies indicated a relationship between increased serum levels of osteoprotegerin with arterial calcification and as a result, it leads to the risk of cardiovascular disease. In our study group we selected patients with osteoporosis, with similar age and body mass index for the assessment of the relationship between cardiovascular disease and osteoprotegerin serum level. We took into account the analysis of correlation and association between the presence of distinct patterns of atherosclerosis and associated diseases like high blood pressure, diabetes mellitus, low HDL cholesterol, increased LDL cholesterol, increased triglycerides and was the case of presence of any type of dyslipidemia, in case of pre-existent treatment. Objective of study was the assessment of osteoprotegerin value as predictive marker for cardiovascular and metabolic risk in osteoporotic patients. Our results showed significant correlations of parathyroid hormone, osteocalcin and biochemical markers of bone with glucose metabolism and lipid were found in our research, maintaining crosstalk between calcium and biochemical markers of bone and cardiovascular risk. The serum level of Osteoprotegerin has been shown to have a large predictive value for the metabolic syndrome as a cardiovascular risk standard in patients with osteoporosis. The osteoprotegerin serum levels were increased in the patients with metabolic syndrome as a protective response facing the atherosclerotic lesions.